2006
DOI: 10.1253/circj.70.1133
|View full text |Cite
|
Sign up to set email alerts
|

Inducibility of Atrial Flutter in Patients With Atrioventricular Nodal Reentrant Tachycardia

Abstract: revious studies have shown that typical atrial flutter (AFL) is caused by a reentrant circuit confined to the right atrium. 1,2 Percutaneous catheter mapping studies have shown that the reentrant circuit includes an area of slow conduction bounded on the lateral side by the septal leaflet of the tricuspid valve and the inferior vena cava (lateral isthmus) and on the medial side by the Eustachian valve/ridge and the septal leaflet of the tricuspid valve (medial isthmus) and the coronary sinus ostium and the sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In all patients, rapid RA pacing from the CS os and mid-free wall was performed to determine the inducibility of AFL. 19 An A20 catheter was positioned at the posterior or posterolateral RA site at which DPs or fractionated potentials (FPs) were apparently recorded along the catheter during rapid RA pacing from the CS os in patients without AFL and during AFL in patients with AFL. Endocardial bipolar electrograms were recorded with a bandpass filter of 30-500 Hz simultaneously with the 12-lead ECG, His bundle electrograms and CS electrograms, and stored digitally on a CardioLab System (Prucka Engineering, Inc, Sugar Land, TX, USA).…”
Section: Electrophysiologic Studymentioning
confidence: 99%
“…In all patients, rapid RA pacing from the CS os and mid-free wall was performed to determine the inducibility of AFL. 19 An A20 catheter was positioned at the posterior or posterolateral RA site at which DPs or fractionated potentials (FPs) were apparently recorded along the catheter during rapid RA pacing from the CS os in patients without AFL and during AFL in patients with AFL. Endocardial bipolar electrograms were recorded with a bandpass filter of 30-500 Hz simultaneously with the 12-lead ECG, His bundle electrograms and CS electrograms, and stored digitally on a CardioLab System (Prucka Engineering, Inc, Sugar Land, TX, USA).…”
Section: Electrophysiologic Studymentioning
confidence: 99%
“…Previous studies have shown that both AVNRT and AFL had an area of slow conduction located in the low posterior right atrium near the ostium of the coronary sinus 2,3 . The studies could provide theoretical support for the conversion of narrow QRS tachycardia from AVNRT to AFL.…”
Section: Discussionmentioning
confidence: 96%